Johann Sebastian Bach - Masters of Classical Music (1988)
Overture No. 4: Réjouissance/Overture No 3 Air/ OvertureNo.4 Badinerie/Oboe Concerto in D minor Adagio/ Minuet in D minor. BWV Anh 132/Minuet in G major, BWV Anh 116